Effects of High Concentration Ozone Gas Fumigation on the Quality and Shelf-life of Longan Fruit. (2nd January 2022) - Chamnan, Saranyapak; Varith, Jaturapatr; Jaturonglumlert, Somkiat; Phimphimol, Jakraphong; Sujinda, Narathip
ABSTRACT: The objective of this research was to study the effects of high concentration ozone (HCO) fumigation on the shelf-life of fresh longan. Longan was exposed to ozone gas at varying inlet concentrations of 4, 000, 8, 500, and 13, 000 ppm with holding times of 5 and 15 min. Results showed that the longan exposed to ozone gas at 8, 500 ppm for 5 min was considered a suitable treatment to extend shelf-life up to 35 days, which is 57% longer than the shelf-life of non-ozonated longan. The SEM revealed that the ozonated longan had less surface epidermal hairs than the non-ozonated longan.